HUBUNGAN PELAYANAN INFORMASI OBAT BERBASIS SYARIAH TERHADAP KEPUASAN PASIEN DI RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG - Aldi Pratama Alpiqi; Rina Wijayanti (Yayasan Nusantara Hasana Berdikari, 2025)
Patient drug information service is one form of pharmaceutical service. This study was conducted at Sultan Agung Islamic Hospital, Semarang. The delivery of detailed and communicative drug information, including questions about patient time, explanation of benefits, and utilization of three prime questions, showed the effectiveness of pharmacist communication and compliance with pharmaceutical service standards.